Manganese Exposure Aggravates β-Amyloid Pathology by Microglial Activation - Lin, Geng; Li, Xinlu; Cheng, Xiaofeng; Zhao, Ning; Zheng, Wei (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease (AD), the most common dementia, is characterized by amyloid plaques (AP) and hyperphosphorylated tau tangles in the brain. Epidemiological evidence suggests that long-term chronic manganese (Mn) exposure increases the risk of AD. Additionally, the levels of Mn are elevated in the blood, cerebrospinal fluid and brain of AD patients, but the mechanisms underlying Mn enhancement of AD development remain unknown. Using the transgenic 3xTg-AD mouse model and mouse-derived microglia and neuroblastoma cell lines, we found that chronic 5-month Mn treatment increased Aβ burden in the cerebral cortex and hippocampus in these 3xTg-AD mice. Furthermore, we found that the β- and γ-secretase cleavage activities were markedly increased while α-secretase cleavage activity was reduced in the brain of Mn-treated AD mice, which might account for the increased Aβ accumulation. Equally important, acute Mn exposure did not alter -secretase 1 (BACE1) gene expression or amyloidosis in amyloidogenic mutant amyloid precursor protein gene hAPPsw-transfected N2a cells (APPsw-N2a); but in APPsw-N2a cells either co-cultured with microglia BV2 or cultured with microglia-conditioned media, Mn exposure increased BACE1 expression and amyloidosis. We further determined that Mn exposure promoted the activation of microglia both in 3xTg-AD mouse brains and in cultured BV2 microglia cells, and increased the secretion of the inflammatory cytokines interleukin-1 (IL-1β) and tumor necrosis factor- (TNF-α). Taken together, these results suggest that Mn may elevate the release of IL-1β and TNF-α from microglia that in turn stimulates the expression of BACE1 gene and protein and hence A production, providing a novel molecular mechanism for chronic Mn exposure to promote amyloidogenesis and AD pathogenesis.